2015
DOI: 10.1007/s11064-015-1564-7
|View full text |Cite
|
Sign up to set email alerts
|

mTOR and Erk1/2 Signaling in the Cerebrospinal Fluid-Contacting Nucleus is Involved in Neuropathic Pain

Abstract: The cerebrospinal fluid-contacting nucleus (CSF-CN) has been demonstrated to be involved in neuropathic pain, but the underlying molecular mechanisms remain unclear. Previous work has shown that mTOR and ERK1/2 are important signaling pathways regulating neuropathic pain. However, studies on the interactions between these major pathways in neuropathic pain are very rare. Therefore, the purpose of this study is to determine whether mTOR and ERK1/2 exist in the CSF-CN and elucidate their alterations in neuropath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…It has been recently reported that the inhibition of the Akt/mTOR pathway resulted in increased activation of ERK1/2 signaling in differentiating oligodendrocytes, but not vice versa [ 25 ]. In the present, the inhibitor of mTOR also exerted stronger effect on ERK level than that of ERK inhibitor on mTOR level in PLCγ1-transformed OA chondrocytes, indicating that the inhibition of mTOR pathway significantly increased ERK signaling; and the inhibition of the ERK pathway does not have enough impact on mTOR signaling, consistent with the very recent study in neuropathic pain [ 26 ]. Combined with the data of the existence of higher expressed the PLCγ1 and mTOR, and lower expressed ERK in human OA chondrocytes, we suggest that PLCγ1/ERK axis was blocked by the PLCγ1/mTOR axis, and the latter inhibited the effect of the PLCγ1/ERK axis on MMP-13 expression in human OA chondrocytes.…”
Section: Discussionsupporting
confidence: 90%
“…It has been recently reported that the inhibition of the Akt/mTOR pathway resulted in increased activation of ERK1/2 signaling in differentiating oligodendrocytes, but not vice versa [ 25 ]. In the present, the inhibitor of mTOR also exerted stronger effect on ERK level than that of ERK inhibitor on mTOR level in PLCγ1-transformed OA chondrocytes, indicating that the inhibition of mTOR pathway significantly increased ERK signaling; and the inhibition of the ERK pathway does not have enough impact on mTOR signaling, consistent with the very recent study in neuropathic pain [ 26 ]. Combined with the data of the existence of higher expressed the PLCγ1 and mTOR, and lower expressed ERK in human OA chondrocytes, we suggest that PLCγ1/ERK axis was blocked by the PLCγ1/mTOR axis, and the latter inhibited the effect of the PLCγ1/ERK axis on MMP-13 expression in human OA chondrocytes.…”
Section: Discussionsupporting
confidence: 90%
“…One study showed that mTOR signaling regulates pain-related synaptic plasticity in the entorhinal-hippocampal pathway in a model of persistent peripheral nociception induced by peripheral bee venom injections (Lyu et al, 2013). Moreover, the levels of mTOR and extracellular signal-regulated kinase (ERK)1 and ERK2 were increased in the cerebrospinal fluid-contacting nucleus of the brainstem after nerve injury (Li et al, 2015). In the spinal cords of rats with chronic constriction injury, inhibition of mTOR with rapamycin reduces the expression of postsynaptic density protein 95 (PSD95; Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Since the supraspinal mechanism of mTOR and ERK1/2 in the persistence of neuropathic pain was reported [19]. ERK1/2, whose activation modulated noxious stimuli induced peripheral/central sensitization [20], regulated neuronal activity in neuropathic pain [21,22].…”
Section: Effects Of Dezocine On P-erk1/2 As a Results Of Neuropathic Painmentioning
confidence: 99%
“…The mTOR signaling pathway, activated in CCI-induced neuropathic pain [17,18], is involved in the transmission and modulation of pain [16,28,29]. Moreover, the blockage of mTOR signaling pathway alleviates neuropathic pain [30], and there is a supraspinal mechanism of mTOR and ERK1/2 in the development and persistence of neuropathic pain [19], with the latter regulating neuronal activity in neuropathic pain [20,21] and pain sensitization [31]. The findings exhibited that there were higher p-mTOR and p-ERK1/2 levels in CCI group than in control group, which were lowered by dezocine in dezocine+CCI group, indicating that dezocine might attenuate neuropathic pain by inactivating mTOR signaling pathway and ERK1/2 signaling pathway in rats.…”
Section: Discussionmentioning
confidence: 99%